2019
DOI: 10.1016/j.stemcr.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Mitochondrial Permeability Transition Pore in hiPSC-Derived Endothelial Cells Induces Glycocalyx Formation and Functional Maturation

Abstract: Human induced pluripotent stem cells (hiPSCs) are used to study organogenesis and model disease as well as being developed for regenerative medicine. Endothelial cells are among the many cell types differentiated from hiPSCs, but their maturation and stabilization fall short of that in adult endothelium. We examined whether shear stress alone or in combination with pericyte co-culture would induce flow alignment and maturation of hiPSC-derived endothelial cells (hiPSC-ECs) but found no effects comparable with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 80 publications
1
14
1
Order By: Relevance
“…Differences are observed between iPSC-derived ECs and primary ECs. RNA sequencing has shown that while iPSC-ECs show differing expression patterns from stem cells ( 54 ), they also do not cluster with primary ECs ( 55 ). Key endothelial markers and flow-sensitive genes, such as NOS3, are expressed, but often at lower levels than found in primary ECs ( 54 ).…”
Section: Differentiation and Characterization Of Vascular Ecs From Humentioning
confidence: 99%
See 1 more Smart Citation
“…Differences are observed between iPSC-derived ECs and primary ECs. RNA sequencing has shown that while iPSC-ECs show differing expression patterns from stem cells ( 54 ), they also do not cluster with primary ECs ( 55 ). Key endothelial markers and flow-sensitive genes, such as NOS3, are expressed, but often at lower levels than found in primary ECs ( 54 ).…”
Section: Differentiation and Characterization Of Vascular Ecs From Humentioning
confidence: 99%
“…Key endothelial markers and flow-sensitive genes, such as NOS3, are expressed, but often at lower levels than found in primary ECs ( 54 ). Metabolic genes also have significantly different expression in iPS-derived ECs compared to primary ECs ( 55 ). Pluripotent markers such as Oct4 and Klf4 ( 54 ) have been detected in iPS-derived ECs which signifies some immaturity.…”
Section: Differentiation and Characterization Of Vascular Ecs From Humentioning
confidence: 99%
“…mPTP inhibition by cyclosporine-A increased ROS generation, but addition of antioxidants rather than prooxidant can enhance cardiomyogenesis [ 75 ]. Prolonged closure of mPTP with cyclosporine-A in human iPSC-derived endothelial cells resulted in more mature mitochondria, prevention of ROS leakage, and functional improvements [ 76 ]. These studies suggested that the redox signaling is a cardiogenic regulatory factor lying the downstream of mPTP inhibition.…”
Section: Ros Mediate Cardiac Differentiation Of Pscsmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity A in human iPSC-derived endothelial cells resulted in more mature mitochondria, prevention of ROS leakage, and functional improvements [76]. These studies suggested that the redox signaling is a cardiogenic regulatory factor lying the downstream of mPTP inhibition.…”
mentioning
confidence: 93%
“…Recent research has identified influential parameters and strategies that regulate and promote hPSC-derived cell maturation. For example, cellular metabolism can regulate the phenotype of hPSC-derived cells, and glycolysis-to-oxidative phosphorylation mitochondrial switching enhances the maturity of hPSC-derived endothelial cells [ 178 ]. Similar metabolic switching via inhibition of hypoxia-inducible factor 1-alpha and its downstream target lactate dehydrogenase A mediated maturation of hPSC-derived cardiomyocytes [ 179 ], suggesting that cellular metabolism may be an important manipulatable factor for regulating the biological relevance of hPSC-derived cells for drug development.…”
Section: Biological Advances: Improving Access To Disease-relevant Humentioning
confidence: 99%